Integration of Naqli and Aqli in the Study of the Quran and Sunnah: A Descriptive Analysis - Md Yousuf Ali; Md Bahar Uddin; Md Redowanul Karim (Fakulti Pengajian Quran dan Sunnah, 2025)
E-Proceeding The9th International Conference on Nabawi Heritage(SWAN 2024) Theme: Prophetic Legacy in Development of Civil Society in the Era of Artificial Intelligence (AI) 6-7 November 2024